The effect of maternal nutrition level during the periconception period on fetal muscle development and plasma hormone concentrations in sheep. (6th May 2016) - Sen, U.; Sirin, E.; Yildiz, S.; Aksoy, Y.; Ulutas, Z.; Kuran, M.
Abstract : The effect of maternal nutrition level during the periconception period on the muscle development of fetus and maternal–fetal plasma hormone concentrations in sheep were examined. Estrus was synchronized in 55 Karayaka ewes and were either fed ad libitum (well-fed, WF, n =23) or 0.5×maintenance (under-fed, UF, n =32) 6 days before and 7 days after mating. Non-pregnant ewes (WF, n =13; UF, n =24) and ewes carrying twins (WF, n =1) and female (WF, n =1; UF, n =3) fetuses were removed from the experiment. The singleton male fetuses from well-fed ( n =8) and under-fed ( n =5) ewes were collected on day 90 of gestation and placental characteristics, fetal BWs and dimensions, fetal organs and muscles weights were recorded. Maternal (on day 7 after mating) and fetal (on day 90 of pregnancy) blood samples were collected to analyze plasma hormone concentrations. Placental characteristics, BW and dimensions, organs and muscles weights of fetuses were not affected by maternal feed intake during the periconception period. Maternal nutrition level did not affect fiber numbers and the muscle cross-sectional area of the fetal longissimus dorsi (LD), semitendinosus (ST) muscles, but the cross-sectional area of the secondary fibers in the fetal LD and ST muscles from the UF ewes were higher than those from the WF ewes ( P <0.05). Also, the ratio of secondary to primary fibers in the ST muscle were tended to be lower in the fetuses from the UF ewes ( P =0.07). Maternal nutrition level during the periconception period did not cause any significant changes in fetal plasma insulin and maternal and fetal plasma IGF-I, cortisol, progesterone, free T3 and T4 concentrations. However, maternal cortisol concentrations were lower while insulin concentrations were higher in the WF ewes than those in the UF ewes ( P <0.05). These results indicate that the reduced maternal feed intake during the periconception period may alter muscle fiber diameter without affecting fiber types, fetal weights and organ developments and plasma hormone concentrations in the fetus.